Dalit Autobiographies as Counter Publics: An Exploratory Essay - Meenakshi Thapan (South Asia Multidisciplinary Academic Journal)
Despite Bourdieu’s warning that autobiography is a form of narcissism and a decline into navel gazing, as it were, the genre of autobiography is a well-recognized medium in contemporary scholarship. In particular, there has been recognition of the autobiographies of subaltern populations as representations of their lived experience, which was hitherto unknown to broader audiences. Such autobiographical texts are increasingly popular ways of understanding the lives of marginalized, excluded “others” that are obfuscated by the veils of difference, entitlement and privilege. This paper seeks to examine this trend through the lens of some Dalit autobiographies and to examine how autobiographical narratives bring out, with rich insight, poignancy and great detail, the everyday lives of Dalit men and women. At the same time, such autobiographical writings unwittingly push the Dalit subaltern into a narrative form that emphasizes the experience of wretchedness, isolation and exclusion. By bringing in the struggle, individual and collective acts of agency against caste dominance, the autobiographies simultaneously constitute “subaltern counter publics,” to use Nancy Fraser’s persuasive term. This confirms that autobiographies are a formidable medium for not only the representation of Dalit experience of subalternity but also of the possibilities for transformation as these emerge through the experience of Dalit writers. The conundrum is whether autobiography is an enabling genre for understanding lived experience or more worryingly poses the problem of reproducing subaltern subjectivity. I conclude that Dalit autobiographies indeed mark a movement towards change through the fierce struggle and independence that they also represent.